(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Aim: To describe the technique and findings of fine needle aspiration cytology (FNAC) of the testes for the assessment of azoospermic male infertility. Methods: Fifty four azoospermic patients were included in this study. A single dose of diclofenac sodium (50mg) Supository was given per rectally half an hour before aspiration. The FNA was done on both testes under surface anesthesia with 23G needle attached to a 10ml disposable syringe. Aspirated smears were stained with H&E. Results: Normal spermatogenesis in both testes was found in 6(11.11%), only in right testis 03(5.55%) and only in left testis 03(5.55%) cases. Hypo spermatogenesis in 07(12.96%) cases . Sertoli cell syndrome in 05(9.26%) and maturation arrest in 30 (55.60%) cases. No significant complications were noted. Conclusion: FNAC of testis is a simple, well tolerated and informative procedure in assesing azoospermia. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19419